Plastic chip detects waterborne viruses.
Waterborne viral diseases pose a serious threat to public health around the world. An EU-funded consortium has therefore developed an advanced, reliable nanotechnology-based sensor that can rapidly detect pathogens in water, thereby enabling better monitoring of water quality.